Mathematical power and its relationship to mathematical culture among high school mathematics teachers - Khuder Hassan, Areej (International Journal of Psychosocial Rehabilitation, 2020)
The current research aims to know the correlation between mathematical power and mathematical culture for secondary school mathematics teachers, and the descriptive research approach was adopted to answer research questions. For data collection, two assessments were built first for the mathematical power, which finalized into 10 assessment paragraphs in an article type and a test for mathematical culture. Its final form consists of (8) items of the article type as well. The sample consisted of 200 high school teachers from the General Directorate of Education for Rusafa (3). The results showed that teachers (male and female) possess the power of mathematics and mathematic culture. It also showed a positive correlation between the research variables.